2020
DOI: 10.1007/s00253-020-10929-w
|View full text |Cite
|
Sign up to set email alerts
|

Sugar alcohols derived from lactose: lactitol, galactitol, and sorbitol

Abstract: Lactose is a common natural disaccharide composed of galactose and glucose molecules. It is mainly found in the whey, the byproduct of cheese and casein industries. As the supply of lactose far exceeds demand, a lot of lactose was discarded as the waste every year, which not only leads to resource waste, but also causes environmental pollution. Therefore, the deep processing of lactose as the feedstock has become a hot research topic. The lactose-derived sugar alcohols, including lactitol, sorbitol, and galact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 61 publications
0
15
0
2
Order By: Relevance
“…Sorbitol, a well-known polyol sweetener, has glycemic regulation properties [30]. Recently, it is regarded as a preferable substitute to high-fructose corn syrup and sucrose that improves preservation effects in the production of dried fruit products [16,31]. Barr et al confirmed that sucrose and dextrose cause a reduction in cyanocobalamin content [14].…”
Section: Effect Of Additives On the Degradation Of Cyanocobalaminmentioning
confidence: 99%
“…Sorbitol, a well-known polyol sweetener, has glycemic regulation properties [30]. Recently, it is regarded as a preferable substitute to high-fructose corn syrup and sucrose that improves preservation effects in the production of dried fruit products [16,31]. Barr et al confirmed that sucrose and dextrose cause a reduction in cyanocobalamin content [14].…”
Section: Effect Of Additives On the Degradation Of Cyanocobalaminmentioning
confidence: 99%
“…Lactulose (4-O-β-d-galactopyranosyl-dfructose), even though being used mostly as a drug for the treatment of hepatic encephalopathy and chronic constipation, is properly considered a prebiotic [28]. Other lactose-derived bioactive compounds that are considered as health-promoting agents are: lactosucrose [29], lactitol (4-O-β-dgalactopyranosyl-D-sorbitol) [30], lactobionic acid (4-O-β-galactopyranosil-d-gluconate) [31], tagatose (3S,4S,5R)-1,3,4,5,6-pentahydroxy-hexan-2-one) [32] and fructosyl-galacto-oligosaccharides (fGOS) [33].…”
Section: Lactose-derived Prebioticsmentioning
confidence: 99%
“…It shares some of the properties of NDOs and as such has been used within the food sector as a low-calorie sweetener and also as a mild laxative, and has been proposed as adequate for consumption by diabetic patients. In the medical field, it has been used in the treatment of hepatic encephalopathy as an alternative to lactulose; also several non-food applications have been claimed for lactitol [30,57].…”
Section: Other Lactose-derived Health Promoting Bioactive Compoundsmentioning
confidence: 99%
“…Lactitol is disaccharide sugar alcohol obtained from the hydrogenation of lactose using nickel as a catalyst. Its production is composed of galactose and sorbitol [ 41 – 43 ]. Lactitol is an odourless white crystalline powder with a sweetness that is 30–40% of sucrose [ 15 , 41 ].…”
Section: Sugar Alcoholsmentioning
confidence: 99%